In‐channel wood‐related hazards at bridges: A review. (11th June 2018) - De Cicco, Pina Nicoletta; Paris, Enio; Ruiz‐Villanueva, Virginia; Solari, Luca; Stoffel, Markus
Abstract: In‐channel wood is a key component in fluvial ecosystems; however, transport of in‐channel wood during floods can create hazards in urbanized areas. Among the main problems is wood accumulation at bridges, which reduces flow openings, causes blockage and inundation of nearby areas and, eventually, results in structures collapsing. Increasing awareness of the importance of the ecological role of wood in rivers calls for a compromise between the preservation of river ecosystems and management strategies for the prevention of wood‐related hazards. In recent years, knowledge related to in‐channel wood dynamics and hazards has notably increased, and a significant body of valuable information can be found in an extensive number of studies. This review provides a comprehensive summary of the most relevant advances regarding in‐channel wood‐bridge interactions. We review the factors controlling wood accumulation formation and summarize the different approaches used to analyse this process, namely, physical and numerical modelling. Finally, we conclude by highlighting the most important knowledge gaps, addressing particularly underresearched fields and stressing the remaining challenges.